The Pride of Students Choosing Sociology as Their Major At the Faculty of Social and Political Sciences University of Riau - Hidir, Achmad; Susanti, Rina; Kadarisman, Yoskar; Amin, Moch. Lathif; Dzulqarnain, M.Faizal (Jurnal Ilmiah Global Education, 2025)
Sociology students at the Faculty of Social and Political Sciences, University of Riau, are proud of the department they have chosen. The sociology program equips them to become competent graduates capable of serving as agents of change in society. This study employs a qualitative approach using structured interviews and free essays from students about their experiences. Informants were purposively selected from the 2022 cohort of students actively involved in campus organizations, without considering their Cumulative Grade Point Average (CGPA). Data were analyzed using thematic analysis to identify patterns and themes related to students' pride. With the growing interest in sociology among young people, it is important for the faculty to continue improving the quality of the curriculum and providing adequate support for students so that they feel proud and engaged in the field they have chosen. This study shows that student involvement in various extracurricular activities, as well as the support and guidance provided by faculty members, are key factors in building students' pride in their department.